2015
DOI: 10.1016/j.jweia.2014.11.006
|View full text |Cite
|
Sign up to set email alerts
|

Bridge deck flutter derivatives: Efficient numerical evaluation exploiting their interdependence

Abstract: Highlights: An efficient CFD approach for the computation of flutter derivatives is presented.  Relationships between flutter derivatives allow halving the number of simulations.  Successfully applied at a ratio 4.9:1 rectangular cylinder and the G1 box section.  Great potential in industrial applications and shape optimal design problems. Highlights (for review) 16It has been found that the proposed methodology offers results which agree well with the 17 experimental data and the accuracy of the estimat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 52 publications
(25 citation statements)
references
References 42 publications
1
16
0
1
Order By: Relevance
“…In all cases the mean value of y + is y + ≤ 2, obtaining for the medium mesh the values presented in Table 3. The values obtained are very similar to the ones reported by Nieto et al [21] for a rectangular cylinder of width to depth ratio 4.9:1.…”
Section: Verification Study and Static Case Resultssupporting
confidence: 91%
“…In all cases the mean value of y + is y + ≤ 2, obtaining for the medium mesh the values presented in Table 3. The values obtained are very similar to the ones reported by Nieto et al [21] for a rectangular cylinder of width to depth ratio 4.9:1.…”
Section: Verification Study and Static Case Resultssupporting
confidence: 91%
“…Thanks to the increasing power of modern computers, Computational Fluid Dynamics (CFD) techniques are becoming an increasingly attractive tool for studying the aerodynamic behavior of bridge decks [4][5][6][7][8][9][10][11][12].…”
Section: Introductionmentioning
confidence: 99%
“…The effectiveness of the sst (shear-stress-transport) and the standard (std) RANSbased turbulence models in predicting flutter derivatives had been compared, and the k-sst formulation proved to be more accurate than the k-std [9]. A 2D unsteady Reynolds-averaged Navier-Stokes (URANS) approach adopting Menter's SST k-turbulence model was employed for computing the flutter and the static aerodynamic characteristics, and the conclusions indicated that the results provided by the proposed methodology agree well with the experimental data [10]. The performances of standard Smagorinsky-Lilly and Kinetic Energy Transport turbulence models were applied to study the unsteady flow field around a rectangular cylinder [11].…”
Section: Introductionmentioning
confidence: 90%